TEACHERS' PERCEPTION ON THE IMPLEMENTATION OF LESSON STUDY : A case study in Junior High School English Teachers Association in Kota Sukabumi - Sobandi, Ade (2014)
This report is the study of the Teachers' Perception on The Implementation of Lesson Study (A case study in Junior High School English Teachers in Kota Sukabumi), which investigated thirty English teachers in Kota Sukabumi. Lesson Study is cycle of professional development in which teachers work together in a team to plan a lesson, apply the lesson in the classroom and evaluate the process of learning through collegiality, and collaborative work. The aims of this study are to to capture the process of Lesson Study implemented in Kota Sukabumi and to investigate the perception of the participants toward Lesson Study program. The study employed a qualitative research design which embraces characteristics of a case study. The data were gathered from several data collection techniques: class observations, questionnaires and interviews to collect some supporting data. The result shows that the English Teachers' perception is positive and they fully understand the term of Lesson Study. However, there are some teachers who doubt about the effect of Lesson Study in developing teachers' professional competence. In the process of Lesson Study, somehow teachers' responsibility and motivation are not fully appeared and take into account that Lesson Study is not their need. They tended to come to the venue only if the headmaster or the district officer asked them to come. From the findings it is recommended that teachers should realize that they need to develop their teaching competence through certain ways which one of them is Lesson Study. Through Lesson Study teachers could learn from each other and recognize the way the students learn in the classroom.